Strategic Management and Digitalization: Elevating Islamic Education Quality in the Global Era - Fuad Sahrul Wafa; Endi Suhendi (Jurnal Iman dan Spiritualitas, 2026)
The development of globalization and the digital era requires Islamic educational institutions to implement strategic management and digital transformation to improve the quality and competitiveness of institutions. This study uses a qualitative, comparative case study design across two institutions: the Addzimat Dai Indonesia Islamic Boarding School and SMPIT Qordova. Data collection was conducted through in-depth interviews, participant observation, and documentation analysis. The results show that integrating strategic management, digital transformation, and transformational leadership significantly improves the quality of education. SMPIT Qordova has successfully implemented the EMIS and LMS systems, while the Addzimat Islamic Boarding School has begun implementing digital learning that remains rooted in Islamic values. However, the study also found several obstacles, particularly in digital infrastructure and technological literacy, which are not evenly distributed across the two institutions. Strategic management integrated with a culture of quality and the use of digital technology has been proven to improve the efficiency of Islamic education governance. Digital transformation plays a role in strengthening transparency, managerial effectiveness, and real-time quality data management. This research offers a conceptual framework that can be replicated by other Islamic educational institutions to formulate evidence-based policies that strengthen quality, innovation, and competitiveness in the global and digital era.